(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
Social fear is one of the aspects that affect the socialization of a person to another person. Social behavior is defined as interactions among individuals that are normally within the same species that are generally beneficial to one another. A person cannot live easily without interaction with another individual; most of the species are interdependent and rely on one another to fulfill the needs of an individual. Obstacles to the interaction of an individual with another individual will defy the success of communication. Obstacles in communications usually happen because of the way an individual behaves and will lead to an irrational result. This study used a quantitative design because this type of method is created for a systematic investigation. Researchers investigated a phenomenon by gathering quantifiable data and performed statistics in the form of numbers. The research instrument was survey questionnaires to determine the causes of the irrational behavior of 50 MWF and 46 T-Th-S Humanities and Social Sciences students. In the statistical treatment of data, we used percentage, weighted mean, and z-test for interpreting the data. The researchers concluded that the students’ social behavior was not affected by any external force because the two groups mentioned had MWF and T-Th-S class schedules. The different class schedules between the group did not affect their social behavior because based on the related literature and studies, class schedules did not affect students’ social behavior. Given that social behavior affects the daily living of students, this research’s objective is to look for solutions that may prevent students from behaving differently other students. Social behavior is a broad study that focuses on one’s behavior in a society. From day-to-day basis, students interact to socialize to gain something.